The diazocarbene (CNN) molecule: characterization of the X 3Sigma- and A 3Pi electronic states - Yamaguchi, Yukio; Schaefer, 3rd, Henry F (The Journal of chemical physics, 2004)
The ground (X (3)Sigma(-)) and first excited triplet (A (3)Pi) electronic states of diazocarbene (CNN) have been investigated systematically starting from the self-consistent-field theory and proceeding to the coupled cluster with single, double, and full triple excitations (CCSDT) method with a wide range of basis sets. While the linear X (3)Sigma(-) ground state of CNN has a real degenerate bending vibrational frequency, the A (3)Pi state of CNN is subject to the Renner-Teller effect and presents two distinct real vibrational frequencies along the bending coordinate. The bending vibrational frequencies of the A (3)Pi state were evaluated via the equation-of-motion coupled cluster (EOM-CC) techniques. The significant sensitivity to level of theory in predicting the ground-state geometry, harmonic vibrational frequencies, and associated infrared intensities has been attributed to the fact that the reference wave function is strongly perturbed by the excitations of 1pi-->3pi followed by a spin flip. At the highest level of theory with the largest basis set, correlation-consistent polarized valence quadruple zeta (cc-pVQZ) CCSDT, the classical X-A splitting (T(e) value) was predicted to be 68.5 kcal/mol (2.97 eV, 24 000 cm(-1)) and the quantum mechanical splitting (T(0) value) to be 69.7 kcal/mol (3.02 eV, 24 400 cm(-1)), which are in excellent agreement with the experimental T(0) values, 67.5-68.2 kcal/mol (2.93-2.96 eV, 23 600-23 900 cm(-1)). With the EOM-CCSD method the Renner parameter (epsilon) and averaged bending vibrational frequency (omega(2)) for the A (3)Pi state were evaluated to be epsilon=-0.118 and omega(2)=615 cm(-1), respectively. They are in fair agreement with the experimental values of epsilon=-0.07 and nu(2)=525 cm(-1).